2019
DOI: 10.1177/1558944719877890
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanical Comparison of the Compressive Force Generated by Various Headless Compression Screws and the Impact of Fracture Gap Size

Abstract: Background: There is evidence that interfragmentary fracture gap size may affect the compression achievable with a modern headless compression screw (HCS). This mechanical study compared the compression achieved by 3 commercial HCS systems through various fracture gaps: CAPTIVATE Headless (Globus Medical, Inc, Audubon, Pennsylvania), Synthes (DePuy Synthes, Westchester, Pennsylvania), and Acumed Acutrak 2 (Acumed LLC, Hillsboro, Oregon). Methods: Screws were inserted into a custom test fixture composed of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…According to Ilyas, Mahoney and Bucklen [ 35 ], the compressive force involved in fracture fixation when it is using Ø2.4 mm orthopedic screws, equivalent to the screw object of the present case study, is of the order of 65 to 70 N; thus, it is assumed that the screw is able to sustain the loads necessary for the correct stabilization of fractures until a degradation of approximately 30% to 35% of mass loss [ 22 ]. However, it is important to emphasize that the model in question does not take into account the regeneration and adhesion of bone tissue in the regions adjacent to the orthopedic screw, which could result in changes in the pull-out forces found in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ilyas, Mahoney and Bucklen [ 35 ], the compressive force involved in fracture fixation when it is using Ø2.4 mm orthopedic screws, equivalent to the screw object of the present case study, is of the order of 65 to 70 N; thus, it is assumed that the screw is able to sustain the loads necessary for the correct stabilization of fractures until a degradation of approximately 30% to 35% of mass loss [ 22 ]. However, it is important to emphasize that the model in question does not take into account the regeneration and adhesion of bone tissue in the regions adjacent to the orthopedic screw, which could result in changes in the pull-out forces found in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we maintained a short fracture gap (0.8 mm) to ensure that the impact of fracture gap was limited from affecting the results. Previous studies have shown that Acutrak screws will generate less compression force with larger fracture gaps [ 1 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, peri-articular bone has a mixture of hard subchondral bone as well as cancellous bone. Previous studies have also acknowledged this as a limitation of bone model studies [ 1 , 8 ].…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
See 2 more Smart Citations